The Effect of Asset Structure, Non-Debt Tax Shield, and Dividend Policy on Capital Structure - Robi Maulana Magribi; Wulan Riyadi; Alan Rusdiana; Sintia Nuriyani (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Capital structure decisions are very important for a company, because they can reflect the company's financial position. Debt conditions continue to increase in 2020-2022 in the chemical and pharmaceutical industries which is not balanced with operating results, indicates that the company has not made good capital structure decisions. Therefore, the aim of this research is to determine the influence of asset structure, non-debt tax shield, and dividend policy on capital structure. The population in the research is the chemical and pharmaceutical industry sub-sector of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period with a total of 107 companies. The sampling technique in the research used non-probability sampling with a purposive sampling method, so that a sample of 23 companies and 69 company sample data were obtained. This research uses multiple linear regression analysis techniques with the help of the SPSS 25 program. Based on the results of research that has been conducted, it shows that partially asset structure variable has an effect on capital structure, variable non-debt tax shield has no effect on capital structure, and variable dividend policy has no effect on capital structure.